Implementasi Ice Breaking dalam Pembelajaran Bahasa Arab di MA Assunniyyah Kencong Jember - Wahyudi, Imam; Maesaroh, Siti (INAIFAS Press, 2023)
The purpose of this study is to motivate students to be as enthusiastic in participating in Arabic language learning. That Arabic learning is still conversional, so it can make arabic learning boring and make students not pay attention to the lessons described by the teacher .this research uses qualitative methods because the object of research is focused on the learning process in the form of the application of ice breaking. By applying ice breaking, it can make students more concentrated and foster an interest in learning Arabic in students. The results of the application of ice breaking can be seen that 28% are very capable 52% capable of 20% underprivileged based on the assessment indicator. The use of ice breaking is very helpful in learning because it can attract students to be more motivated and enjoy the lessons delivered by the teacher.